2010
DOI: 10.1007/s00467-010-1483-4
|View full text |Cite
|
Sign up to set email alerts
|

Management of regional citrate anticoagulation in pediatric high-flux dialysis: activated coagulation time versus post-filter ionized calcium

Abstract: Recent years has seen an increasing use of regional citrate anticoagulation in pediatric dialysis. Several approaches have been described for monitoring anticoagulation in the extracorporeal circuit, such as serum citrate levels, post-filter ionized calcium (iCa), and activated coagulation time (ACT). However, no standard recommendations have yet been established for applying any of these parameters, especially for iCa. The objective of this retrospective analysis was to establish adequate coagulation manageme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
10
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 28 publications
4
10
0
Order By: Relevance
“…Figure 7 shows that a Ca 2+ level of about 0.2 mmol/l inhibits coagulation, whereas a Ca 2+ concentration of <0.4 mmol/l might not suppress coagulation sufficiently. These findings are in accordance with those of Kreuzer et al [40] and Opatrny et al [43]. The latter found no prolonged ACT at a post-filter Ca 2+ level slightly lower than 0.4 mmol/l compared to the patient Ca 2+ .…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…Figure 7 shows that a Ca 2+ level of about 0.2 mmol/l inhibits coagulation, whereas a Ca 2+ concentration of <0.4 mmol/l might not suppress coagulation sufficiently. These findings are in accordance with those of Kreuzer et al [40] and Opatrny et al [43]. The latter found no prolonged ACT at a post-filter Ca 2+ level slightly lower than 0.4 mmol/l compared to the patient Ca 2+ .…”
Section: Discussionsupporting
confidence: 83%
“…In agreement with Kreuzer et al [40] and our in vitro study [41,42], we could show that Ca 2+ predicts the anticoagulation status determined by ACT, which reflects the entire plasmatic coagulation cascade as well as platelet function. Therefore, we used samples of the patients from the extracorporeal circuit pre-filter as well as after calcium infusion.…”
Section: Discussionsupporting
confidence: 80%
“…In all patients, the citrate (3%) to blood flow ratio was started at 1:25 (= 4.0% of blood flow) and subsequently adapted during the course of the session to match post-filter ionized calcium levels ≤0.30 mmol/l. The rate was calculated to achieve a citrate plasma level of about 6 mmol/l, which is needed for sufficient anticoagulation [12,13]. The patients' ionized calcium levels were monitored closely.…”
Section: Methodsmentioning
confidence: 99%
“…For sufficient anticoagulation, iCa levels of 0.2–0.4 mmol/l are necessary in the extracorporeal circuit [8,9,10,11,12]. Kreuzer et al [13] found that a postfilter iCa of <0.3 mmol/l corresponds to an activated clotting time of >120 s. Our own investigations confirmed a highly significant correlation between iCa and activated clotting time in vitro, which clearly demonstrates the importance of focusing on iCa as a target in regional citrate anticoagulation [14]. The use of calcium-free dialysate prevents an increase in iCa within the filter.…”
Section: Introductionmentioning
confidence: 99%
“…Since the reduction in iCa concentration is limited to the extracorporeal circuit, this type of anticoagulation is called regional anticoagulation. The rate of calcium infusion depends on the systemic iCa level in the patient as well as on the calcium clearance of the dialyzer [13]. The target range for a patient’s systemic blood iCa level is generally 1.1–1.3 mmol/l [15,16].…”
Section: Introductionmentioning
confidence: 99%